Long‐Term Follow‐Up of Patients With Short QT Syndrome: Clinical Profile and Outcome. Issue 23 (4th December 2018) - El‐Battrawy, Ibrahim; Besler, Johanna; Liebe, Volker; Schimpf, Rainer; Tülümen, Erol; Rudic, Boris; Lang, Siegfried; Wolpert, Christian; Zhou, Xiaobo; Akin, Ibrahim; Borggrefe, Martin
Abstract : Background: Short QT syndrome (SQTS) is a rare inheritable disease associated with sudden cardiac death. Data on long‐term outcomes of families with SQTS are limited. Methods and Results: Seventeen patients with SQTS in 7 independent families (48% men; median age, 42.4 years; corrected QT interval, 324.9±40.8 ms) were followed up for 13.5±2.5 years. A history of sudden cardiac death was documented in 71% of families. A large number of them showed sudden cardiac deaths at a younger age, with a predominance of men (67%). Five patients had syncope (29%) and 9 (53%) had atrial fibrillation or atrial flutter. An SQTS‐related gene was found in 76% of the patients as follows: KCNH2 (SQTS 1) in 4, CACNA1C (SQTS 4) in 3, and CACNb2 (SQTS 5) in 6. Five patients (29%) received an implantable cardioverter‐defibrillator and 5 patients received long‐term prophylaxis with hydroquinidine. During follow‐up, 1 patient received an appropriate implantable cardioverter‐defibrillator shock attributable to ventricular fibrillation. The patient received no further implantable cardioverter‐defibrillator shocks after treatment with hydroquinidine. Conclusions: The risk of sudden cardiac death in SQTS families is high. However, after appropriate risk assessment and individualized treatment options (hydroquinidine and/or implantable cardioverter‐defibrillator), the long‐term outcome is relatively benign when patients are seen at a reference center.